Bibliometric Study on Corporate Governance of Islamic Banks - Alam, Azhar; Nugroho, Danu Wahyu; Isman, Isman; Ahmi, Aidi (International Journal of Economics and Financial Issues, 2025)
This paper explores the analysis of trends related to the research on corporate governance of Islamic banks from 1994 to January 2024. This study aims to find out (1) the growth and publication trends in the field of corporate governance of Islamic banks today; (2) the most productive contributor to the corporate governance of Islamic banks; (3) documents that are widely cited in the research on corporate governance of Islamic banks; and (4) important keywords and themes involved in the study of corporate governance of Islamic banks. The data was obtained through the Scopus database with the keywords (islamic OR sharia*) AND (bank* OR finance) AND “corporate governance.” The search resulted in 346 documents, which became 261 documents after screening. The data was exported and analyzed using VOSviewer, Publish or Perish (PoP), and Microsoft Excel. The results of the study show that the most publications occurred in 2020. The largest contributors to publishing the most research papers were Rihab Grassa from authors (12 publications), International Islamic University Malaysia from institutions (15 publications), English from languages (259 publications), Malaysia from countries (62 publications), and Journal of Islamic Accounting and Business Research from the title of the most prolific contributor (23 publications). The article “Shari’ah Supervision, Corporate Governance, and Performance: Conventional versus Islamic Banks” was written by Sabur Mollah and Mahbub Zaman as the most cited publication. Based on the results of the network visualization mapping, the research on corporate governance of Islamic banks is divided into five main themes: profit management and ownership structure in Islamic banks, financial performance of Islamic banks, sharia governance in Islamic banks, operational risk management of Islamic banks, and management and supervision of Islamic banks.